(untitled) (TAJ: Journal of Teachers Association, 2018)
Non-alcoholic fatty liver disease (NAFLD) is an emerging chronic liver disease and may lead to liver cirrhosis and hepatocellular carcinoma. It is now the most common chronic liver disease in many developed as well as developing countries. This hospital based study was done to see the prevalence of non-alcoholic fatty liver disease (NAFLD) and metabolic syndrome among patients attending in a tertiary care center in Bangladesh. Here, 334 nonalcoholic subjects of both sex and age were included. Metabolic syndrome was assessed by modified ATP III criteria and fatty liver diagnosis was based on ultrasound findings. 27.2% had the metabolic syndrome and was more common in female. Prevalence of NAFLD was 44% and was more common in female. Metabolic syndrome was found in 61.5% with NAFLD. TAJ 2015; 28(2): 44-51